The relationship between systemic therapies and low skeletal muscle mass in patients with intermediate and advanced hepatocellular carcinoma - Chen, Jingjing; Huang, Xueying; Wei, Qiaoxin; Liu, Songtao; Song, Wenyan; Liu, Mei (Frontiers in Immunology, 2025)
BackgroundLow skeletal muscle mass (LSMM) has been associated with poor prognosis in hepatocellular carcinoma (HCC) patients receiving systemic therapy. However, its impact across different treatment regimens remains unclear.MethodsA retrospective study analyzed 714 patients with intermediate and advanced HCC, divided into immunotherapy (I, n=85), target-immunotherapy combination (I+T, n=545), and targeted therapy (T, n=84) groups based on treatment. Skeletal muscle was assessed via computed tomography (CT) at the third lumbar vertebral level (L3) before and after 3 months of treatment. LSMM was evaluated by the third lumbar skeletal muscle index (L3-SMI) using a predefined threshold. Patients were stratified by baseline values and treatment changes. Kaplan-Meier and Cox models were used to compare overall survival (OS) and progression-free survival (PFS).ResultsThere was no significant difference in the loss of muscle mass among the three groups of LSMM patients; whereas, non-LSMM(NLSMM) patients in group T lost more muscle mass than those in group I (P=0.040).In the I+T group, patients who achieved an objective response (ORR) had less muscle mass loss than those without (P=0.013), while the changes in muscle mass for patients in the I group and T group were unrelated to treatment response. Baseline or post-treatment LSMM was associated with poorer median OS, especially in the I+T group. Progressive LSMM was linked to shorter median PFS (4.9 vs 5.7 months) and OS (9.8 vs 16.5 months), with similar results in the I+T group (mPFS, 4.2 vs. 5.8 months; mOS, 9.7 vs 16.1 months). Patients with LSMM had a higher incidence of treatment-related SAEs, particularly ascites and fatigue.ConclusionIn patients with combined LSMM in hepatocellular carcinoma, muscle loss did not significantly differ between those treated with I, I+T, and T; however, T treatment contributed to muscle mass loss in NLSMM patients. Greater muscle loss correlated with poorer treatment outcomes and increased SAEs, and baseline, post-treatment, and progressive LSMM were linked to significantly worse prognoses, particularly with combined treatment regimens.